A Digitalization of the Agricultural Sector to Reduce Farmer Poverty in Indonesia: A Systematic Literature Review - Ilyas (International Journal of Economics, Business, and Entrepreneurship, 2025)
This study aims to describe efforts that can be made so that the agricultural sector is able to utilize technology and agricultural digitalization offered by the Industrial Revolution 4.0, so as to reduce farmer poverty in Indonesia. This research method uses a quantitative approach. The data used are secondary data, sourced from books, journals, documentation or publications from the Central Statistics Agency (BPS), the Ministry of Agriculture, and publications from other institutions relevant to this study. The data analysis used is a systematic literature review. The results of this study indicate that the use of technology in the agricultural sector is still minimal. Furthermore, by utilizing the industrial revolution, there are several steps that can be taken to prepare farmers to welcome Indonesia Emas 2045, including: improving the linkage between farmer groups and agro-industry; increasing incentives for research and development activities in the agricultural sector; developing agricultural products that focus on superior commodities; resolving fertilizer issues; building synergy with banks and other financial institutions; encouraging the use of mobile phones or smartphones in agricultural production; and intensifying the performance of technology and information service providers.